Acquired Visual Deficits Independent of Lesion Site in Acute Stroke - Wijesundera, Chamini; Vingrys, Algis J.; Wijeratne, Tissa; Crewther, Sheila G. (Frontiers in Neurology, 2020)
Clinical diagnosis of stroke is primarily concerned with persistent (>24hours) motor and cognitive deficits rather than with visual processing that drives attention, most motor actions and cognitive thinking .Furthermore, visual function occupies larger cortical and subcortical areas than motor function in the brain. Thus to determine the effects of acute stroke on functional vision, we utilized an iPad application (Melbourne Rapid Field-Neural) to assess vision at the bedside in Sunshine Hospital, Melbourne, of 160 sequentially presenting first episode, acute (< 7 days) ischemic stroke patients (mean age 68 ±14.5 years, range 29-95, 89 males) of whom 60 showed no evidence of prior ocular disease. Site of lesion was ascertained with magnetic resonance imaging or non-contrast computer tomography. One hundred patients were excluded from the study due to existing eye disease, inadequate radiological confirmation, language comprehension difficulty, or been too ill to participate. Assessment of visual acuities (high contrast and visual acuity-in-noise) and central 24⁰ visual field sensitivity took about 6 minutes per eye.The non-parametric Mann-Whitney-U test was used in comparison with 37 aged similar controls. The significant loss in visual field sensitivity was present in 68% (41/60, p<.0001) patients, with 44% (18/41) of these patients unaware of their field losses. Although high contrast visual acuity was unaffected in most (55/60) patients, visual acuity-in-noise was reduced in 62%, (37/60, p<.0001). Visual field defects were associated with all occipital, parietal and posterior cerebellar artery strokes but also with 9/15 middle cerebral artery lesions and 11 lesions in other brain regions indicating that the site of lesion is not the sole determinant of visual deficit in a number of patients. Most importantly our findings demonstrate a high incidence of acute first episode ischemic stroke patients are associated with acquired visual field deficits. Such visual field deficits can be independent of the confirmed lesion site and suggest that visual dysfunction may also be associated with more generalized cerebral oedema.The results also highlight the need for rapid and rigorous bedside testing of vision for patients and demonstrate the translational value of the “Melbourne Rapid Field- Neural” iPad application. The clinical trial registration: ACTRN12618001111268 at http://www.ANZCTR.org.au/ACTRN12618001111268.aspx.